The quality of canned fruit beverages in the Philippines - Dancel, Guia Nora; Silverio, Remedios Q. (1968)
Two brands of canned papaya beverage, three of mango and four guayabano produced in the Greater Manila Area were evaluated on their physico-chemical, microbiological and sensory qualities. Physico-chemical tests showed that the canned fruit beverages fulfilled the requirements for normal sound appearance of cans, standard per cent fill, headspace and pH. Brix, titrable acidity and Brix-acid ratio of three juices in the study met the United States standards for pineapple juice. United States standard for percent pulp was met only in one juice sample. Vacuum readings and net weights deviated from the values recommended for fruit beverages. No significant rank correlation was found to exist between the physico-chemical and sensory qualities when all the samples were ranked together. When ranked per type beverage, however, Brix reading of the papaya beverage, were found significantly correlated negatively to flavor and acceptability and positively to consistency. Per cent acid of the mango beverages was found significantly correlated negatively to flavor. The results of the microbiological examination indicate that the products were manufactured under sanitary conditions.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Beverages -- Philippines; Canned fruit juices